Völur and Seiðr: How Pre-Christian Shamanistic Practices Gave Viking-Age Women Agency - Nowaczewski, Emilia (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2025)
The Viking Age was a patriarchal time when men dominated the social and political world. However, due to the shamanistic practice known as seiðr, women of this time had access to unique roles as spiritual leaders. This essay discusses the impact seiðr had on Viking Age women’s agency and self-empowerment. Seiðr has close ties to textile arts, with seiðr rituals taking influence from repetitive spinning and weaving circles. The relationship between seiðr and textile art is seen throughout Norse mythology, and women who practice seiðr (called völur) are agential characters throughout many Icelandic sagas—most notably Thorbjörg from Eirik the Red’s Saga and Gunnhildr in Njal’s Saga. The rise of Christianity in Scandinavia and its subsequent anti-witchcraft laws soon led to the dissipation of seiðr.